2019
DOI: 10.1136/bmjopen-2018-027666
|View full text |Cite
|
Sign up to set email alerts
|

Importance of vitamin D in acute and critically ill children with subgroup analyses of sepsis and respiratory tract infections: a systematic review and meta-analysis

Abstract: ObjectivesTo estimate the prevalence of 25-hydroxyvitamin D (25(OH)D) deficiency and investigate its association with mortality in children with acute or critical conditions.DesignSystematic review and meta-analysis of observational studies.Data sourcesPubMed, OVID, Google Scholar and the Cochrane Library searched until 21 December 2018.Eligibility criteriaStudies of children hospitalised with acute or critical conditions who had blood 25(OH)D levels measured.Data extraction and synthesisWe obtained pooled pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 85 publications
(71 reference statements)
0
38
0
4
Order By: Relevance
“…As of March 06, 94 patients were discharged from hospital, median hospital stay was 15 (IQR, [11][12][13][14][15][16][17][18] days. MODS developed in 17 (7.1%) patients, septic shock in 6 (2.5%) patients.…”
Section: Resultsmentioning
confidence: 99%
“…As of March 06, 94 patients were discharged from hospital, median hospital stay was 15 (IQR, [11][12][13][14][15][16][17][18] days. MODS developed in 17 (7.1%) patients, septic shock in 6 (2.5%) patients.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, critically ill patients have a very high prevalence of vitamin D deficiency, and low vitamin D levels are clearly associated with greater illness severity, morbidity, and mortality in both adult and pediatric intensive care unit (ICU) patients, as well as medical and surgical ICUs [23]. However, as in most other populations, the most important question remains unanswered: whether low vitamin D is an innocent bystander, simply reflecting greater disease severity, or represents an independent and modifiable risk factor amenable to rapid normalization through loading dose supplementation [24,25].…”
Section: Vitamin D Deficiency In Critical Illnessmentioning
confidence: 99%
“…In addition, it has been suggested that because PI are calculated based on trials that are generally homogeneous, that is, patient populations and comparator treatments are interchangeable, the overall effect estimates may not be accurate if they do not meet this criterion (99) . As an example of PI use in nutrition, Cariolou et al recently conducted an AD meta-analysis on the association between 25-hydroxyvitamin D deficiency and mortality in children with acute or critical conditions (100) . Based on a random-effects model, the pooled OR and 95 % CI of the risk of mortality in vitamin D deficient v. vitamin D non-deficient acute and critically ill children was 1•81 (95 % CI 1•24, 2•64).…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Based on a random-effects model, the pooled OR and 95 % CI of the risk of mortality in vitamin D deficient v. vitamin D non-deficient acute and critically ill children was 1•81 (95 % CI 1•24, 2•64). However, based on 95 % PI (0 •71, 4•20), there was much less certainty, that is, wider intervals that also included 1, regarding this association (100) .…”
Section: Methods and Resultsmentioning
confidence: 99%